The importance of measuring the levels of ionized magnesium in the blood in critically ill patients - Stanojević Marija B.; Parezanovic Miro; Biorac Marko; Spasić Svetolik; Kovačević Sanjin; Lopičić Srđan; Nešović Ostojić Jelena (Journal of Medical Biochemistry)
Background: Critical illnesses imply vital organ dysfunctions with high risk of imminent death. Magnesium is a bioessential element with multiple physiological effects relevant for vital body functions. It stabilizes excitable membranes contributing to proper neuromuscular, cardiovascular and respiratory functions. Ionized Mg2+ (iMg2+) is free bioactive form of Mg2+ in body fluids. Magnesium disorders in critically ill patients are often overlooked. Chronic Mg2+ deficiency is a condition of growing incidence in the general population and a significant factor in overall morbidity and mortality in critical illness. Main goal of this study was to investigate the existing literature related to determination of iMg2+ in the critically ill and to raise awareness of the problem of chronic Mg2+ deficiency in these patients. Methods: Search was conducted across electronic PubMed library database from 1975 to November 2024 using keywords concerning iMg2+ and critical care patients, to identify studies investigating the measuring of blood concentration of iMg2+ fraction in patients with critical health conditions. Search was limited to English language. Selection criteria included only studies on human, and excluded studies on animal population. Results: We identified 95 relevant studies. Reviewed papers show that abnormalities of Mg2+ levels are prevalent in critical illnesses. Their severity can impose vital threat. Disconcordance between total Mg2+ (tMg2+) and iMg2+ blood levels is frequently present in critical patients. Conclusions: Appropriate electrolyte analyzer assay is needed to promptly determine iMg2+ levels to assess Mg2+ status in critically ill patients, in order to help detect and correct Mg2+ imbalances and estimate the requirement for Mg2+ recompense in the case of deficiency, and thereby provide better outcome of the disease.